Potential of Chromolaena odorata, Ipomoea carnea and Eichhornia crassipes as green manures on soil fertility index and rice production on vertisols - Suntoro, Suntoro; Herdiansyah, Ganjar; Mujiyo , Mujiyo; Widijanto, Hery; Maroeto , Maroeto; Julianto, Eko Amiadji; Puspitasari, Chelyna; Tjahjanto, Azhar Dimas; Wardhana, Haikal Rafi (Journal of Aridland Agriculture, 2024)
The organic farming system is an agricultural activity which aims to preserve soil fertility and create sustainable farming. The objective of this research is to evaluate the effects of the application of green manure on soil fertility index and rice production. The research was carried out in Weru District, Sukoharjo Regency, using an experiment method with a Randomized Complete Block Design (RCBD). The research included 10 treatments: T0 = Control, T1 = NPK fertilizer 0.2 ton/ha, T2 = rice straw 10 ton/ha, T3 = Chromolaena odorata 10 ton/ha, T4 = Ipomoea carnea 10 ton/ha, T5 = Eichhornia crassipes 10 ton/ha, T6 = NPK 0.1 ton/ha + rice straw 5 ton/ha, T7 = NPK 0.1 ton/ha + C. odorata 5 ton/ha, T8 = NPK 0.1 ton/ha + I. carnea 5 ton/ha, T9 = NPK 0.1 ton/h + E. crassipes 5 ton/ha, with three repetitions. The soil characteristics tested were pH, total N, available P, exchangeable K, exchangeable Ca, exchangeable Mg, Cation Exchange Capacity (CEC), Base Saturation (BS), and Soil Organic Carbon (SOC). The results show that C. odorata, I. carnea, and E. crassipes have potential as green manures, due to their high N content, of 3.38%, 3.54%, and 2.95% andthe ability to increase soil fertility and rice production. The soil fertility index increased from high to very high, neither within single applications nor combined with NPK fertilizer. The highest rice production was obtained with the use of C. odorata, which increased harvest dry weight by 2.24 ton/ha (67.67%) or an increase of 2.1 ton/ha (75%) in milled dry weight, followed by I. carnea and E. crassipes. There was a correlation between soil fertility index and rice production, shown by the higher SFI, the harvest dry weight and milled dry weight increases.